Resveratrol Oligomers, Plant-Produced Natural Products With Anti-virulence and Plant Immune-Priming Roles - Kang, Ji Eun; Yoo, Nayeon; Jeon, Byeong Jun; Kim, Beom Seok; Chung, Eui-Hwan (Frontiers in Plant Science, 2022)
Antibiotic resistance has become increasingly prevalent in the environment. Many alternative strategies have been proposed for the treatment and prevention of diverse diseases in agriculture. Among them, the modulation of bacterial virulence to bypass antibiotic resistance or boost plant innate immunity can be considered a promising drug target. Plant-produced natural products offer a broad spectrum of stereochemistry and a wide range of pharmacophores, providing a great diversity of biological activities. Here, we present a perspective on the putative role of plant-produced resveratrol oligomers as anti-virulence and plant-immune priming agents for efficient disease management. Resveratrol oligomers can decrease 1) bacterial motility directly and 2) indirectly by attenuating the bacterial type III secretion system (TT3S). They induce enhanced local immune responses mediated by two layered-plant innate immunity, demonstrating 3) a putative plant immune priming role.